Pengaruh Penyajian Laporan Keuangan dan Aksesibilitas Informasi Keuangan Terhadap Akuntabilitas Pengelolaan Keuangan Desa - Sulistyowati, Andita; Riskanita, Dinda; Andriani, Juwita (Jurnal Ilmiah Raflesia Akuntansi, 2024)
This study aims to obtain empirical evidence on the impact of financial report presentation and financial information accessibility on the accountability of village fund management. Village fund management accountability refers to the responsibility of village governments to the public regarding village financial management. The research was conducted in 13 villages in Kledung District, Temanggung Regency, with 52 respondents selected using a non-probability sampling method, specifically purposive sampling. Data were collected through questionnaires, and data analysis was performed using multiple linear regression with SPSS version 26. The results show that both financial report presentation and financial information accessibility have a positive effect on the accountability of village financial management.